Pengaruh Return On Equity dan Dividend Payout Ratio Terhadap Return Saham yang Tercatat pada Indeks Saham Syariah Indonesia (ISSI) Periode 2019-2023 - Defi Erlita; Muzakir Muzakir (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to examine the influence of ROE and DPR on stock returns. The population in this study is all companies listed in ISSI. The sample in this study is companies listed on ISSI for the 2019-2023 period. The analysis techniques used are classical assumption tests, multiple linear regression, hypothesis tests and determination coefficient tests. The results of the first hypothesis test show that there is an effect of ROE on stock returns, while the results of the second hypothesis show that there is no influence of the House of Representatives on stock returns. And the third hypothesis shows that there is an effect of return on equity and dividend payout ratio on stock returns.